Analisis Minimalisasi Biaya (AMiB) Antihipertensi Irbesartan dengan Candesartan pada Pasien Hipertensi Rawat Jalan - Nurlaela, Nurlaela; Fauziah, Fauziah; K, Khamdiyah Indah; Kusuma, Ikhwan Yuda (Journal of Pharmaceutical and Health Research, 2024)
Cost minimization of antihypertensive therapy is very essential to optimize patient care and allocation of hospital resources. This study aimed to compare the most cost-minimized cost of irbesartan and candesartan therapy treatment in hypertensive patients at Goeteng Taroenadibrata Purbalingga in the periods January to December 2023. The research method used quantitative with a retrospective approach. Data were analyzed using normality kormogorov smirnov test and continued by mann whitney test. population in this were hypertensive patients at Goeteng Taroenadibrata Purbalingga with a sample of 100 hypertensive patients.The results showed that out of 100 samples, 37 samples used irbesartan and 63 candesartan samples with an average total direct medical cost of antihypertensive treatment, laboratory costs and consultation costs required by patients using irbesartan therapy Rp. 158,665, and candesartan Rp. 116,874. Statistical analysis has a p-value that shows a significant difference between irbesartan treatment and candesartan treatment. the conclusion in this study is that the most cost-minimizing antihypertensive therapy is the candesartan group compared to the irbesartan group. Further research is needed to analyze a broader CMA of blood pressure control and comorbid diseases.